FORMATION OF EARTH'S EARLY ARCHAEAN CONTINENTAL CRUST - Smithies R.H.; Champion D.C.; Cassidy K.F. (My University, 2003)
Subduction of oceanic crust at an unusually low-angle has been proposed as a model for the growth of continental crust older than about 2.5 Ga. At modern zones of low-angle-, or flat-subduction, magmatic additions to new crust come from partial melting of both the subducting oceanic crust (slab) and the thin wedge of mantle above the slab. Evidence for both a slab and wedge source is preserved in most late Archaean (3.0–2.5 Ga) terrains, but we find little evidence that a mantle wedge contributed to crustal growth prior to ∼3.1 Ga. This lack of evidence in part reflects a dearth of exposed crust aged between 3.0 and 3.3 Ga, but also suggests that subduction enriched mantle source regions did not develop before ∼3.3 Ga and possibly not before 3.1 Ga. In contrast to most modern terrains and some late-Archaean terrains, early Archaean (>∼3.3 Ga) continental crust evolved through direct melting of thick mafic crust. We invoke a process of subduction that does not include the development of a mantle wedge, and call this process Archaean flat-subduction to distinguish it from modern low-angle subduction.
Keywords: Archaean; Crustal evolution; Magmatism; Low-angle subduction; Enriched mantle; Precambrian::Archean; Докембрий::Архей